Cường độ chuyển dời Gamma nối tầng của Ni trong phản ứng Ni - Trần, Văn Nguyên (Trường Đại học Đà Lạt, 2013)
The data recorder by Summation of Amplit udes of Coincidence Pulses (SACP) used research n uclear structure which it has establis hed at 3rd channel or Da lat reactor. This report showed gamma cascades intensities of 58Ni reaction